Exploring the Role of Social Media and Individual Behaviors in Flood Evacuation Processes: An Agent‐Based Modeling Approach. Issue 11 (14th November 2017) - Du, Erhu; Cai, Ximing; Sun, Zhiyong; Minsker, Barbara
Abstract: Flood warnings from various information sources are important for individuals to make evacuation decisions during a flood event. In this study, we develop a general opinion dynamics model to simulate how individuals update their flood hazard awareness when exposed to multiple information sources, including global broadcast, social media, and observations of neighbors' actions. The opinion dynamics model is coupled with a traffic model to simulate the evacuation processes of a residential community with a given transportation network. Through various scenarios, we investigate how social media affect the opinion dynamics and evacuation processes. We find that stronger social media can make evacuation processes more sensitive to the change of global broadcast and neighbor observations, and thus, impose larger uncertainty on evacuation rates (i.e., a large range of evacuation rates corresponding to sources of information). For instance, evacuation rates are lower when social media become more influential and individuals have less trust in global broadcast. Stubborn individuals can significantly affect the opinion dynamics and reduce evacuation rates. In addition, evacuation rates respond to the percentage of stubborn agents in a nonlinear manner, i.e., above a threshold, the impact of stubborn agents will be intensified by stronger social media. These results highlight the role of social media in flood evacuation processes and the need to monitor social media so that misinformation can be corrected in a timely manner. The joint impacts of social media, quality of flood warnings, and transportation capacity on evacuation rates are also discussed. Key Points: Social media is integrated with global broadcast and neighbor observations in a consistent model to simulate agents' opinion dynamics Our model simulates lower evacuation rates when social media are more influential and individuals have less trust in global flood warnings Evacuation rates respond to the percentage of stubborn agents in a nonlinear manner